Development of an integrated model for emission reduction through energy efficiency and renewable energy - Rzayeva, Ulviyya; Balayev, Rasul; Ahmadzade, Emin; Mirzammadova, Konul (Eastern-European Journal of Enterprise Technologies, 2025)
The study’s focus is the country’s energy sector, including renewable energy production. The problem to be solved is modeling the impact of energy efficiency and renewable energy production on greenhouse gas emissions in the country. This study investigates the impact of energy efficiency and the transition to renewable energy sources on greenhouse gas emissions in Azerbaijan, where the energy mix remains dominated by fossil fuels. Using a regression–based analytical framework, the research quantifies the contribution of these factors to changes in emission levels over time. The empirical results demonstrate that improvements in energy efficiency, measured as gross domestic product (GDP) generated per unit of total energy consumption, exert the greatest influence on emission reductions. This finding suggests that economic growth driven by efficient energy use can serve as a key mechanism for decarbonization. In contrast, the expected mitigating effect of the share of renewable energy sources in the national energy balance was not statistically significant. This outcome is likely explained by the relatively small share of renewables in Azerbaijan’s total energy supply and the early stage of the country’s renewable sector. The study concludes that effective climate policy should combine measures to accelerate improvements in energy efficiency with initiatives to expand the use of renewable energy. The proposed model highlights the dual importance of optimizing existing energy consumption while investing in cleaner technologies. Based on the results, 80% of the annual change in a country’s greenhouse gas emissions can be explained by changes in factors such as renewable electricity generation, the share of renewable electricity in total electricity generation, and GDP per unit of energy consumption. The findings can be applied to the design of sustainable energy strategies and long-term decarbonization policies.